Implementasi Pembelajaran Make up Sehari-hari sebagai Sarana Peningkatan Rasa Percaya Diri Siswi SMK Dharma Wanita Gresik - Shafiyah AM, Layyinatus; Evawati, Diana; Nuraini, Iut (Jurnal Tata Rias, 2025)
The purpose of this research is to investigate the relationship between the self-confidence of female students at SMK Dharma Wanita Gresik and daily make up learning. Self-confidence is an important component in adolescent development, and female students are expected to enhance their self-confidence by learning make up. This study employs a quantitative approach, and data were collected through questionnaires distributed to fifty respondens.to find therelationship between the variables of make up learning and self-confidence, the obtained data were analyzed statistically. The results of the study indicate that make up lessons have a significant positive effect on the self-confidence of female students. Make up lessons resulted in a good level of self-confidence in 74% of respondents. Furthermore the research found that female students with better make up skills tend to have higher self-confidence. These findings suggest that vocational education, which includes practical skill learning such as make up, can aid in the development of students’ character and professionalism. It is hoped that this research will contribute to the development of vocational education curricula, enhance students’ practical skills, and improve their self-confidence in vocational high schools (SMK). Keywords : vocational education, self-confidence, practical sklills.